Massive spin-2 particles via embedment of the Fierz-Pauli equations of motion - Dalmazi, D. [UNESP]; Santos, A. L. R. dos [UNESP]; Mendonça, E. L. [UNESP] (Iop Publishing Ltd, 2015)
Here we obtain alternative descriptions of massive spin-2 particles by an embedding procedure of the Fierz-Pauli equations of motion. All models are free of ghosts at the quadratic level, although most of them are of a higher order in derivatives. The models that we obtain can be nonlinearly completed in terms of a dynamic and a fixed metric. They include some f(R) massive gravities recently considered in the literature. In some cases there is an infrared (no derivative) modification of the Fierz-Pauli mass term altogether, with higher order terms in derivatives. The analytic structure of the propagator of the corresponding free theories is not affected by the extra terms in the action, as compared to the usual second order Fierz-Pauli theory.
Keywords: Fierz-Pauli; Massive spin-2; Massive gravity